A mended and broken heart : the life and love of Francis of Assisi - Murray, Wendy, 1956- (New York : Basic Books, 2008)
A humane and uncensored portrait of St. Francis of Assisi, Catholicism's most popular--and least understood--saint
Assisi's son -- Partying and war -- Dreams and prayers -- Light breaks -- Endings -- Beginnings -- Reversal -- Gentle fire -- The round table -- The sultan -- Revolt -- Perfect love -- Final assertion -- Those he left behind -- Anyone's saint.
Includes bibliographical references (p. 241-242) and index.
Keywords: Francis, -- of Assisi, Saint, -- 1182-1226.; Christian saints -- Italy -- Assisi -- Biography